Maple City, Cowley County - Stanton, Colina (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a short history of Maple City in Spring Creek Township, Cowley County. Only four miles from the Oklahoma border, this small post-village never had access to a railway. The hilly, rolling terrain made horses and ranching a way of life, but the town could not compete with Winfield or Arkansas City and began to fade by World War I. This sketch relies on two excellent family histories, many newspaper clippings, interviews, and site studies of the terrain.
Colina Stanton, “Maple City, Cowley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/169.
Keywords: Great Depression; Maple City School; Spanish Influenza; Tent Revivals; Cowley County; Maple City